2009
DOI: 10.1007/s11248-009-9266-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of MON810 and comparable non-GM maize varieties cultured in the field are more similar than are those of conventional lines

Abstract: Maize is a major food crop and genetically modified (GM) varieties represented 24% of the global production in 2007. Authorized GM organisms have been tested for human and environmental safety. We previously used microarrays to compare the transcriptome profiles of widely used commercial MON810 versus near-isogenic varieties and reported differential expression of a small set of sequences in leaves of in vitro cultured plants of AristisBt/Aristis and PR33P67/PR33P66 (Coll et al. 2008). Here we further assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 27 publications
4
40
0
1
Order By: Relevance
“…Metabolome analysis of Bt-maize by NMR also revealed significant differences in free amino acid contents of the parental line; however, other likely-influential factors were not assessed in this study (9). Comparative transcript profiling of different maize cultivars harboring an identical Bt transgene insertion event revealed that the variability between cultivars was much greater than the influence of the transgene (10,11). Independently, comparison of the potato tuber proteome of 21…”
mentioning
confidence: 67%
“…Metabolome analysis of Bt-maize by NMR also revealed significant differences in free amino acid contents of the parental line; however, other likely-influential factors were not assessed in this study (9). Comparative transcript profiling of different maize cultivars harboring an identical Bt transgene insertion event revealed that the variability between cultivars was much greater than the influence of the transgene (10,11). Independently, comparison of the potato tuber proteome of 21…”
mentioning
confidence: 67%
“…When performing transcriptomic studies using in vitro-or field-grown maize (Zea mays) plants, Coll et al (2008Coll et al ( , 2009 found differential expression for a minority of transcripts between in vitro-grown MON810 (insectresistant of Bt type) and control lines, and most of these differences were not observed in the field. In real agricultural conditions, under two farming practices (conventional and low-nitrogen fertilization), Coll et al (2010a) found differential expression for only 0.14% of the analyzed sequences (approximately one-third of the maize genome).…”
Section: Maizementioning
confidence: 99%
“…The obtained lyophilized pellets were dissolved in solubilisation buffer [2 M thiourea, 0.4% (v/v) Triton X-100, 7 M urea, 4% (w/v) CHAPS, 1% immobilized pH gradient (IPG) buffer [3][4][5][6][7][8][9][10][11]. The protein was measured according to Ramagli [17], with albumin from chicken egg white (Sigma) as standard.…”
Section: Gel Electrophoresis Of Proteins From Maize Flourmentioning
confidence: 99%
“…The European Food Safety Authority panel on GMOs, recommends searching for known allergens [2] and evaluating the possible effects of the genetic modification in GM plants [3] by comparing compositional data of the GM plant versus the non-GM counterpart, using either targeted or non-targeted profiling techniques. There are already several examples that validate the use of proteomics [4][5][6][7], transcriptomics [4,8,9] and metabolomics [4,10,11] techniques to perform substantial equivalence analysis of transgenic plants.…”
Section: Introductionmentioning
confidence: 99%